The brides of High Hill - Vo, Nghi (Vo, Nghi. Singing Hills cycle ;, 2024)
"The cleric Chih accompanies a beautiful young bride to her wedding to the aging ruler of a crumbling estate situated at the crossroads of dead empires. The bride's party is welcomed with elaborate courtesies and extravagant banquets, but between the frightened servants and the cryptic warnings of the lord's mad son, they quickly realize that something is haunting the shadowed halls. As Chih and the bride-to-be explore empty rooms and desolate courtyards, they are drawn into the mystery of what became of Lord Guo's previous wives and the dark history of Doi Cao itself. But as the wedding night draws to its close, Chih will learn at their peril that not all monsters are to be found in the shadows; some hide in plain sight" --